Training In Making It-Based Learning Media In Successful Independent Learning For Vocational School Teachers In Kabupaten Pesisir Selatan - Alwen Bentri; Abna Hidayati; Eldarni Eldarni; Vevi Sunarti (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2022)
IT-based media creation training at this time is very necessary for teachers to optimize the learning process. The phenomenon in the field of teachers tends to only upload teaching materials, so that sometimes they do not achieve the expected competency targets. This service aims to provide teachers with skills in developing IT-based learning media. The method used in this training is face-to-face and also online and also online via zoom. At the initial stage, face-to-face material is given about the design of IT-based learning media. Introduction of applications for creating IT-based learning media by media lecturers from the Education Technology Study Program. The respondents involved in the training were high school teachers in Pesisir Selatan Regency. The teachers are selected by representatives from high schools in the sub-district with the hope that they can pass on their abilities to other teachers in their schools. The number of respondents in this activity were 35 high school/vocational teachers in Pessel Regency. The implementation of offline and online training has been carried out according to the planned procedure. The offline training stage is carried out at the location, namely SMA N 1 Painan. At this stage the training is carried out by giving an initial presentation to shape students' perceptions of the importance of knowledge about media and digital evaluation. Furthermore, the provision of applications for practice in the form of IT-based media development software. In the final stage, namely practice. Furthermore, at the next stage, training was carried out through zoom meetings for 2 times, namely to strengthen knowledge and also present activities that have been carried out by students. The outputs in this PKM program are teachers who have skills in making digitalization-based teaching materials with a satisfaction level of activity implementation which is 4.54 (scale 1-5). Keywords: Training, learning media, IT-Based, Teacher